Écriture Féminine as subversion: Reclaiming agency in Javanese historiography through TUTUR DEDES: doa dan kutukan - Maulana, Moh. Faiz; Hidayana, Irwan Martua; Santoso, Widjajanti M. (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
This article examines the use of écriture féminine—a feminist writing practice that foregrounds women’s bodily experience and subjective voice—in Amalia Yunus’ novel Tutur Dedes: Doa dan Kutukan as a form of resistance against androcentric literary discourse. The novel challenges conventional stereotypes by portraying Dedes not as a passive object of male desire but as an active historical and political agent engaged in shaping social change. Through strategies such as first-person narration, symbolic representations of birth and motherhood, and the reclamation of female corporeality, the narrative confronts patriarchal constraints that have long defined women’s roles in literature. In this context, écriture féminine functions as a subversive practice that destabilizes what Cixous calls “phallogocentric structures”—systems of thought privileging male-centered logic—while simultaneously enabling women to reclaim their voices and identities. Likewise, the study employs Mignolo’s concept of “epistemic disobedience,” understood here as the deliberate act of resisting dominant frameworks of male-centered knowledge, to show how Yunus’ text reconfigures cultural memory. By reimagining Dedes as a figure of intellectual and political agency, the novel disrupts the androcentric canon that often marginalizes women as secondary characters. This study argues that Tutur Dedes: Doa dan Kutukan not only redefines female representation through narrative form and thematic symbolism but also contributes to a broader feminist discourse by demonstrating literature’s capacity to act as a site of resistance and transformative critique across cultural and disciplinary boundaries.